# Maclaurin series of $\frac{1}{(2-x)^2}$

When googling about Maclaurin series, I found this: $$\begin{eqnarray*} \frac{1}{1-x} = \sum_{n=0}^\infty x^n \\ \frac{1}{x} = \frac{1}{1-(1-x)} = \sum_{n=0}^\infty (1-x)^n \\ \frac{1}{x^2} = \sum_{n=0}^\infty (1-x^2)^n \\ \frac{1}{(2-x)^2} & = & \sum_{n=0}^\infty (1-(2-x)^2)^n) \\ & = & \sum_{n=0}^\infty (-x^2 +4x - 3)^n \\ & = & \sum_{n=0}^\infty (-1)^n (x - 3)^n (x - 1)^n \end{eqnarray*}$$

There appears to be problem regarding the convergence at $$x = 0$$. I don't see where the mistake in the working is, and then how to continue until we get the standard answer for power series of $$\frac{1}{(2-x)^2}$$? Thank you

I would like to suggest another (standard) approach which seems much easier:

$$\frac{1}{(2-x)^2} = \left(\frac{1}{2-x}\right)'$$ $$\frac{1}{2-x} = \frac{1}{2}\cdot \frac{1}{1-\frac{x}{2}}=\frac{1}{2}\sum_{n=0}^{\infty}\frac{x^n}{2^n}$$ $$\Rightarrow \frac{1}{(2-x)^2} = \frac{1}{2}\sum_{n=1}^{\infty}\frac{nx^{n-1}}{2^n} = \sum_{n=0}^{\infty}\frac{(n+1)x^{n}}{2^{n+2}}$$

• Thank you for the answer May 30 '19 at 8:40

That series from the starting is valid if $$|x|<1$$

And you got the hint now.

Find the convergence interaiew..usign this from the starting..and you will see why X=0 gives divergence result

At last you should get $$|1-(2-x)^2|<1$$ Here is the graph showing the above region: which on solving gives the approximate solution interval as $$0.58

So,

$$x=0$$ not lies in this interval

• Stupid me, should have checked the radius of convergence from the beginning. Thank you May 30 '19 at 8:38
• @Magenta can u please do a vote up or accept it as final asnwer .. if you think you got your answer in any of the solutions provided on this page May 30 '19 at 10:07
• By clicking on upper triangle icon May 31 '19 at 4:03
• Ok, think I have done that. Please tell me if there is something not correct. Thank you May 31 '19 at 6:39
• thanks ... you may see a tick mark,,, below that upper triangle... you may chose any answer by clicking tick mark... so as to accept the answer of this posted question May 31 '19 at 7:25

Here is a big hint go get you started.

$$\frac {1}{(2-x)^2} = \frac{d}{dx} \frac {1}{2-x}$$

• Thank you for the hint May 30 '19 at 8:40